Activation of pruritogenic TGR5, MrgprA3, and MrgprC11 on colon-innervating afferents induces visceral hypersensitivity - Joel Castro; Andrea M. Harrington; TinaMarie Lieu; Sonia Garcia-Caraballo; Jessica Maddern; Gudrun Schober; Tracey O’Donnell; Luke Grundy; Amanda L. Lumsden; Paul Miller; Andre Ghetti; Martin S. Steinhoff; et al. (JCI Insight, 2019)
Itch induces scratching that removes irritants from the skin, whereas pain initiates withdrawal or avoidance of tissue damage. While pain arises from both the skin and viscera, we investigated whether pruritogenic irritant mechanisms also function within visceral pathways. We show that subsets of colon-innervating sensory neurons in mice express, either individually or in combination, the pruritogenic receptors Tgr5 and the Mas-gene–related GPCRs Mrgpra3 and Mrgprc11. Agonists of these receptors activated subsets of colonic sensory neurons and evoked colonic afferent mechanical hypersensitivity via a TRPA1-dependent mechanism. In vivo intracolonic administration of individual TGR5, MrgprA3, or MrgprC11 agonists induced pronounced visceral hypersensitivity to colorectal distension. Coadministration of these agonists as an “itch cocktail” augmented hypersensitivity to colorectal distension and changed mouse behavior. These irritant mechanisms were maintained and enhanced in a model of chronic visceral hypersensitivity relevant to irritable bowel syndrome. Neurons from human dorsal root ganglia also expressed TGR5, as well as the human ortholog MrgprX1, and showed increased responsiveness to pruritogenic agonists in pathological states. These data support the existence of an irritant-sensing system in the colon that is a visceral representation of the itch pathways found in skin, thereby contributing to sensory disturbances accompanying common intestinal disorders.